KARAKTERISASI SIFAT FISIS DAN MEKANIS SAMBUNGAN LAS SMAW BAJA A-287 SEBELUM DAN SESUDAH PWHT - Yustiasih Purwaningrum (Faculty of Industrial Technology Universitas Islam Indonesia, 2006)
The aimed of this research are to compare physical dan mechanical properties between raw materials and Shielded Metal Arc Steel Weld Metals and to find optimum temperature of annealing. A series of Shielded Metal Arc Steel Weld Metals were made on 3 mm of Thick A 287 carbon steels. The electrode used was E 6013, Ø 3.2 mm. Annealing was performed with three different temperature were 300°C, 600°C, dan 850°C. The results show that the tensile strength of raw material had the same value with weld metals and weld metals with annealing 300°C and 600°C, but weld metals with annealing 850°C had lower tensile strength. The hardness experiments was used Vickers Micro Hardness.The Hardness number of weld metals was higher than HAZ and raw materials. Weld Metals with annealing 300°C had the highest value. The elongation of weld metals and weld metals with annealing 300°C and 600°C had lower number than raw materials, but weld metals with annealing 850°C had almost the same value of elongation with raw materials. The optimum annealing temperature was 850°C because weld metals with annealing 850°C had high elongation and low tensile strength.Keywords SMAW, Annealing, Vickers Micro Hardness, Tensile Strength, Elongation.